Dokumentacja kartograficzna zmian wydobycia kruszywa naturalnego w powiecie gnieźnieńskim w latach 2005-2015 - Horbiński, Tymoteusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
This article presents the processing of public data from the Internet on the changes in the extraction of natural aggregate in the Gniezno district in 2005–2015. The obtained data include the BDOT, PIG and orthophotomaps. The research and the processing operations were based on a ortophotomap. The outcome was cartographic documentation modelled by a topographic map including the dynamics of the phenomena and photographic documentation. The adopted research methodology was presented for developing cartographic documentation together with the advantages and disadvantages of this type of documentation.
Keywords: topographic map; cartographic documentation; extraction of natural aggregate; orthophotomap; BDOT